2016
DOI: 10.1074/jbc.m115.713578
|View full text |Cite
|
Sign up to set email alerts
|

Generation of Integration-free Induced Neural Stem Cells from Mouse Fibroblasts

Abstract: The viral vector-mediated overexpression of the defined transcription factors, Brn4/Pou3f4, Sox2, Klf4, and c-Myc (BSKM), could induce the direct conversion of somatic fibroblasts into induced neural stem cells (iNSCs). However, viral vectors may be randomly integrated into the host genome thereby increasing the risk for undesired genotoxicity, mutagenesis, and tumor formation. Here we describe the generation of integration-free iNSCs from mouse fibroblasts by non-viral episomal vectors containing BSKM. The ep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
28
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 25 publications
(28 citation statements)
references
References 44 publications
(25 reference statements)
0
28
0
Order By: Relevance
“…Using this excisable reprogramming vector system, the authors could derive transgene-free iNSCs by direct conversion of human adult peripheral blood monocytes, as well as dermal and fetal pancreas fibroblasts. Similar oriP/EBNA of EBV-based episomal vectors were used to express OKSM and LIN28 in combination with a small hairpin against p53 in adult human fibroblasts [42] or Brn4, Klf4, Sox2, and c-Myc in mouse embryonic fibroblasts [58]. Mauksch et al reported the generation of iNSCs by nonviral means employing plasmid transfection and recombinant protein transduction using SOX2 and PAX6 [54].…”
Section: Generation Of Transgene-free Inscsmentioning
confidence: 99%
See 4 more Smart Citations
“…Using this excisable reprogramming vector system, the authors could derive transgene-free iNSCs by direct conversion of human adult peripheral blood monocytes, as well as dermal and fetal pancreas fibroblasts. Similar oriP/EBNA of EBV-based episomal vectors were used to express OKSM and LIN28 in combination with a small hairpin against p53 in adult human fibroblasts [42] or Brn4, Klf4, Sox2, and c-Myc in mouse embryonic fibroblasts [58]. Mauksch et al reported the generation of iNSCs by nonviral means employing plasmid transfection and recombinant protein transduction using SOX2 and PAX6 [54].…”
Section: Generation Of Transgene-free Inscsmentioning
confidence: 99%
“…As a matter of fact, the various protocols for the generation of iNSCs give rise to distinct iNSC populations that slightly differ in self renewal capacity, marker expression, and regional identity, as well as in vitro and in vivo differentiation potential. While Kim et al [11] reported passage of their mouse iNSCs for 3-5 times only, more recent studies demonstrated maintenance of NSC characteristics for more than 30 passages [13,14,28,34,36,38,58,73]. In order to demonstrate selfrenewal potential and clonal growth ability, iNSCs were either cultivated as primary and secondary neurospheres [33,34], analyzed in colony formation assays [28,33,36,39,42,48,72], and/or passaged several times [11,13,14,26,30,32,33,38,57,59,60,73].…”
Section: Molecular and Cellular Characterization Of Inscsmentioning
confidence: 99%
See 3 more Smart Citations